Historical introduction to human diversity I - Swallow, Dallas (Henry Stewart Talks, 2009)
The inherited nature of diversity in humans, Person to person variability, Human biochemical genetics, Inborn errors of metabolism, Alkaptonuria, Phenylketonuria, Recessive inheritance, Abundant and structural proteins, Sickle cell anaemia, Pharmacogenetics and pharmacogenomics, G6PD deficiency